Combined Effect of Bioactive Compounds and Storage Temperature on Sensory Quality and Safety of Minimally Processed Celery, Leek and Butternut Squash - Alvarez, María Victoria (2015)
In this work, the combined effect of bioactive compounds (tea tree essential oil, propolis extract and gallic acid) and storage temperature (15 and 5C) on microbiological and sensory quality of fresh-cut celery, leek and butternut squash was studied. It was confirmed that a good control of refrigeration temperature limits the growth of spoilage and pathogenic microorganisms. Tea tree essential oil and propolis showed significant effectiveness in controlling the microbiota present in vegetables. Also, both endogenous Escherichia coli and inoculated E.coli O157:H7 counts were significantly reduced in vegetables by the combined application of propolis and tea tree essential oil with optimal refrigeration temperature. Propolis improved visual quality extending the sensory shelf life of celery and butternut squash at 5C. Similar improvement effects were shown by tea tree essential oil when applied on leek and squash, at 5C. These findings strongly suggest that propolis and tea tree essential oil have potential to be good preservatives improving microbiological and sensory quality of celery, leek and squash. Practical Applications: The industry of fresh-cut produce confronts new challenges such as the development of technologies that allows the maintenance of fresh produce quality and extends its shelf life to reach more distant markets, ensuring the safety of products to protect the health of consumers. Thus, the development of natural food preservatives in the field of fresh produce responds to consumer demands of healthy and natural products. The findings reported in this work strongly suggest that propolis and tea tree essential oil have potential to be good preservatives improving microbiological and sensory quality of celery, leek and squash.